Test osiągnięć szkolnych jako narzędzie badań nad nauczaniem literatury (na podstawie badań nad rozumieniem treści symbolicznej tekstu literackiego przez uczniów klas III?V) = Test of School Achievements as an Instrument for Researches on the Teaching of Literature - Guttmeier, Ewa (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The review presents a test of school achievements and its application to researches on the understanding of symbolical contents by third, fourth and fifth grade pupils of an elementary school. The authoress gives reasons for the great usefulness of this sort of researches.
Keywords: szkolnictwo; testy; badania